2010
DOI: 10.1002/jat.1550
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in brain cells and behavioral deficits in mice after treatment with high doses of amantadine

Abstract: Amantadine (AMA) is an uncompetitive antagonist of the N-methyl-d-aspartate receptor, with clinical application, acting on treatment of influenza A virus and Parkinson's disease. It has been proposed that AMA can indirectly modulate dopaminergic transmission. In high doses, the central nervous system is its primary site of toxicity. To examine deleterious effects on CNS induced by AMA, this study evaluated possible neurobehavioral alterations induced by AMA such as stereotyped behavior, the effects on locomoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Drugs acting in the central nervous system and in endogenous neurotransmitters can induce DNA damage in brain tissue [1–3]. Glutamate is a neurotransmitter capable of inducing excitotoxicity in neurodegenerative diseases like Parkinson and Alzheimer, mediated by release of calcium, which can initiate a cascade of intracellular signals that result in oxidative stress [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs acting in the central nervous system and in endogenous neurotransmitters can induce DNA damage in brain tissue [1–3]. Glutamate is a neurotransmitter capable of inducing excitotoxicity in neurodegenerative diseases like Parkinson and Alzheimer, mediated by release of calcium, which can initiate a cascade of intracellular signals that result in oxidative stress [4,5].…”
mentioning
confidence: 99%
“…There are few studies on the effects of aminoadamantane drugs on genomic stability. A recent study has shown genotoxic effects of amantadine assessed by comet assay in blood and brain tissues of mice [3]. In this study, we evaluated the possible genotoxic/antigenotoxic and mutagenic effects of memantine.…”
mentioning
confidence: 99%
“…Additionally, it is known that the exposure to stress promotes neuronal changes, including apoptosis, morphological changes, and increased risk of brain damage (Joëls et al 2007). On the other hand, Kaefer et al (2010) observed that DNA damage affected locomotion, thus impairing the animal's behavioral tests, and demonstrating that neurotoxicity can be associated directly with neurobehavioral changes. Therefore, a causality relationship between ethanol withdrawal with anxiety and oxidative DNA damage is impossible to establish at this time, and future studies to elucidate this matter need to be planned.…”
Section: Discussionmentioning
confidence: 93%
“…Amantadine and rimantadine were not recommended for the treatment of IAV infections in 2009, because 100% of the seasonal, as well as the 2009 influenza pandemic strains, carried resistance to the drugs [ 12 ]. Amantadine side effects were also associated with the impairment of central nervous system activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%